Innovation Manufacturing and Engineering Management : Selected, peer reviewed papers from the International Conference on Innovation Manufacturing and Engineering Management (IMEM) 2011, October 21-23, 2011, Chongqing, China (Advanced materials research ;, 2011)
The main themes and trends covered by this volume are Manufacturing Technology and Applications and Innovation Engineering Management. Both inward-looking research (core areas of Materials and Manufacturing Technology) and outward-looking research (multi-disciplinary, inter-disciplinary and applications) are reviewed. The work will provide invaluable guidance to those interested in these subjects. Review from Book News Inc.: Fifty papers from the October 2011 conference propose new approaches to manufacturing processes, scheduling, logistics, cost management, data processing, and port construction. Three papers from Chongqing City Management College explore a suitable temperature for lead-free soldering, analyze common defects in reflow soldering on surface mounted electronic components, and optimize wave soldering parameters. Other topics include a seed-fertilizer box for a no-till seeder, an anti-reflective coating for solar cells, an anti-radiation notebook computer, a rating system for green construction, and forecast sharing between a manufacturer and its retailers.